(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article aims at discussing the relationship between body and writing on the contemporary scene, emphasizing the notion of envelope body. The corpus of analysis is Meu Nome: Mamãe, by Aury Porto, directed by Janaina Leite and dramaturgy by Claudia Barral. The analysis is based on the memorial experience of someone who attended the performance (the enunciator of this article) in interlocution with theoretical contributions on archives and documents within the scope of the performing arts and their intersection with semiotic studies, more precisely in their dialog with Jacques Fontanille’s book Corps et sens (2011). In this book, the author states that the body is the substrate of semiosis.